BCL7A and BCL7B potentiate SWI/SNF-complex-mediated chromatin accessibility to regulate gene expression and vegetative phase transition in plants - Lei, Yawen; Yu, Yaoguang; Fu, Wei; Zhu, Tao; Wu, Caihong; Zhang, Zhihao; Yu, Zewang; Song, Xin; Xu, Jianqu; Liang, Zhenwei; Lü, Peitao; Li, Chenlong (Nature communications, 2024)
Switch defective/sucrose non-fermentable (SWI/SNF) chromatin remodeling complexes are multi-subunit machineries that establish and maintain chromatin accessibility and gene expression by regulating chromatin structure. However, how the remodeling activities of SWI/SNF complexes are regulated in eukaryotes remains elusive. B-cell lymphoma/leukemia protein 7 A/B/C (BCL7A/B/C) have been reported as subunits of SWI/SNF complexes for decades in animals and recently in plants; however, the role of BCL7 subunits in SWI/SNF function remains undefined. Here, we identify a unique role for plant BCL7A and BCL7B homologous subunits in potentiating the genome-wide chromatin remodeling activities of SWI/SNF complexes in plants. BCL7A/B require the catalytic ATPase BRAHMA (BRM) to assemble with the signature subunits of the BRM-Associated SWI/SNF complexes (BAS) and for genomic binding at a subset of target genes. Loss of BCL7A and BCL7B diminishes BAS-mediated genome-wide chromatin accessibility without changing the stability and genomic targeting of the BAS complex, highlighting the specialized role of BCL7A/B in regulating remodeling activity. We further show that BCL7A/B fine-tune the remodeling activity of BAS complexes to generate accessible chromatin at the juvenility resetting region (JRR) of the microRNAs MIR156A/C for plant juvenile identity maintenance. In summary, our work uncovers the function of previously elusive SWI/SNF subunits in multicellular eukaryotes and provides insights into the mechanisms whereby plants memorize the juvenile identity through SWI/SNF-mediated control of chromatin accessibility. This study uncovers the specialized function of previously elusive BCL7 subunits of SWI/SNF complexes in eukaryotes and reveals the mechanism whereby plants memorize the juvenile identity through SWI/SNF-mediated control of chromatin accessibility.